1998
DOI: 10.1080/02786829808965557
|View full text |Cite
|
Sign up to set email alerts
|

A Cascade Impactor for Mineral Particle Analysis

Abstract: A cascade impactor (NCI) made of stainless steel with six stages was developed to collect particles using 50% cutpoints in the range of 0.64 to 19.4 pm. The sixth stage of the NCI was calibrated using monodisperse aerosols. The experimental MMAD (mass median aerodynamic diameter) was 0.634 pm, which agreed with the calculated MMAD. The NCI, stacked filter unit (SFU) and personal air samplers with the cyclone were used to characterize the workers exposure in two Brazilian plants where niobium minerals with thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The particle size distributions were determined using a six-stage cascade impactor with an operational flow rate of 12 l/min, and cut-off diameters of 0.64, 1.0, 2.4, 4.7, 9.9 and 19.4 μm (Dias da Cunha et al 1998b). The cascade impactor was located near the workers at the point of highest total dust concentration and at 1.5 m from the soil.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The particle size distributions were determined using a six-stage cascade impactor with an operational flow rate of 12 l/min, and cut-off diameters of 0.64, 1.0, 2.4, 4.7, 9.9 and 19.4 μm (Dias da Cunha et al 1998b). The cascade impactor was located near the workers at the point of highest total dust concentration and at 1.5 m from the soil.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The CI operational flow rate was 12.5 L min −1 and the total volume was measured by a volume integrator system. The cut-off diameters of each stage of the CI are 19.9, 9.9, 4.7, 2.4, 1.0 and 0.64 μm, respectively (Dias da Cunha et al 1998). The airborne particles in the fine fraction of aerosol (d aer <2.5 μm) were collected using the portable air samplers with cyclone at four sampling sites: Punta Plaza, Ipanema refuge, Flagstaff I, and Flagstaff II.…”
Section: Aerosol Samplingmentioning
confidence: 99%
“…Metal-bearing particle inhalation can cause damage for workers health. Previous studies have shown that these workers are exposed to mineral dust particles (Dias da Cunha et al 1998a, b, 2002. At this plant, the workers are exposed to Ta-bearing particles, by inhalation and by ingestion of drink water containing Ta (Dália 2006).…”
Section: Introductionmentioning
confidence: 99%